2018
DOI: 10.1016/j.stem.2018.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Tissue Adapts to Restrain Progenitors Carrying Clonal p53 Mutations

Abstract: SummaryAging human tissues, such as sun-exposed epidermis, accumulate a high burden of progenitor cells that carry oncogenic mutations. However, most progenitors carrying such mutations colonize and persist in normal tissue without forming tumors. Here, we investigated tissue-level constraints on clonal progenitor behavior by inducing a single-allele p53 mutation (Trp53R245W; p53∗/wt), prevalent in normal human epidermis and squamous cell carcinoma, in transgenic mouse epidermis. p53∗/wt progenitors initially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
116
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(127 citation statements)
references
References 51 publications
(86 reference statements)
11
116
0
Order By: Relevance
“…Applying the MLE approach constrained by the cell-cycle time analysis at each body site yielded improved fits of the SP model to data from paw epidermis in Axin2-cre ERT R26 Rainbow animals and from ear and dorsal interfollicular epidermis in AhYFP mice compared with those fits reported in the original publications ( Fig. S8; Suppl. Methods) 11,21,30 . Despite differences in average keratinocyte division rates across territories (l » 2.0, 1.5, 1.2/week for hind paw, ear and dorsum, respectively), all analyzed regions share comparable intermediate proportions of progenitor basal cells r (~55%, the rest corresponding to differentiating basal cells) and a predominance of asymmetric cell divisions (i.e.…”
Section: Clonal Dynamics In Skin Epidermismentioning
confidence: 99%
See 1 more Smart Citation
“…Applying the MLE approach constrained by the cell-cycle time analysis at each body site yielded improved fits of the SP model to data from paw epidermis in Axin2-cre ERT R26 Rainbow animals and from ear and dorsal interfollicular epidermis in AhYFP mice compared with those fits reported in the original publications ( Fig. S8; Suppl. Methods) 11,21,30 . Despite differences in average keratinocyte division rates across territories (l » 2.0, 1.5, 1.2/week for hind paw, ear and dorsum, respectively), all analyzed regions share comparable intermediate proportions of progenitor basal cells r (~55%, the rest corresponding to differentiating basal cells) and a predominance of asymmetric cell divisions (i.e.…”
Section: Clonal Dynamics In Skin Epidermismentioning
confidence: 99%
“…Skin epidermis was then peeled away using fine forceps and processed as described above for the esophageal epithelium. Lineage-tracing data from Ah-cre ERT R26 flEYFP derived clones in esophagus 5 , ear 30 and dorsal epidermis 21 were obtained from experimental colleagues (data available upon request). Data on induced Axin2-cre ERT R26 Rainbow clones in hindpaw 11 and Lgr6-eGFPcre ERT R26 flConfetti in back epidermis 33 were kindly provided by the authors.…”
Section: Wholemount Preparation and Immunostainingmentioning
confidence: 99%
“…where A represents the basal layer progenitor cells, B the basal cells committed to 15 differentiate and C the suprabasal layer cells. Progenitor cells divide regularly with an 16 overall division rate λ and give rise to either two progenitor daughters (AA), two 17 differentiating daughters (BB) or one daughter of each type (AB) with fixed 18 probabilities. Given the fact that AA symmetric division leads to clone expansion and 19 BB symmetric division tends towards to clone extinction, the two symmetric division 20 rates should be equal in order for a steady state in terms of number of cells to be 21 maintained across the progenitor clone population.…”
mentioning
confidence: 99%
“…If 110 stratification is the next event, B cell stratifies, leaving an empty space, which 111 allows potential neighbouring "double state" daughters to be released. The study of p53 and DN Maml1 mutant clone dynamics in mouse epithelia indicated 115 that the mutant progenitor clones are not in homeostasis in a mixed tissue, and have a 116 fitness advantage over their wild-type counterparts [9,16]. This has been shown to be 117 achieved by having a bias towards the production of proliferating progeny.…”
mentioning
confidence: 99%
“…TP53 mutations protect against cell death and require sunlight for selection because TP53 subclones are smaller 94 in non-sun exposed skin 13 . Normal sun-exposed skin does not exist because the extent of sun exposure varies 95 massively between patients.…”
mentioning
confidence: 99%